ANALISIS KESULITAN SISWA SMP KELAS VII DALAM MENYELESAIKAN SOAL OPERASI ALJABAR - Eli Herawati; Gida Kadarisma (IKIP Siliwangi, 2021)
This article aims to analyze the difficulties of grade VII junior high school students in solving algebraic operation problems. This type of research is descriptive qualitative. The subjects in this study were students of class VII-A at a private junior high school in West Bandung Regency. The researcher used an instrument in the form of 7 items of comprehension ability, where each question represented an indicator of mathematical understanding. The data analysis technique used in this research is the test results of algebraic operations, data reduction and drawing conclusions. Based on the data analysis, it was found that some students had difficulties in solving algebraic operation problems, including students who did not understand what concept was being asked, students still did not understand calculating addition, subtraction and algebraic multiplication operations, students did not understand how to factor, students were less careful in writing operation signs or variables and students are still wrong in defining the variable 'x' they think that 'x' is a sign of the multiplication operation. So it can be concluded that the ability to solve algebraic operation problems in class VII-A is still low and still cannot reach the expected KKM value.